Cangrelor Reduced Ischemic Event Risk, Even with Restrictive MI and ST Definitions - Rizzo, Toni (MD Conference Express, 2014)
The Clinical Trial Comparing Cangrelor to Clopidogrel Standard Therapy in Subjects Who Require Percutaneous Coronary Intervention [CHAMPION PHOENIX; NCT01156571] randomized 11,145 patients undergoing percutaneous intervention in a double-blind, double-dummy fashion to a bolus and infusion of cangrelor followed by clopidogrel or to clopidogrel 600 or 300 mg. This updated analysis examines the robustness of the effect of cangrelor on ischemic events using sequential sensitivity analyses of the primary composite end point by excluding stent thrombosis events that occurred during the procedure and applying increasingly stringent criteria for myocardial infarction.